(untitled) (Research, Society and Development, 2021)
Rangelands contribute significantly to livelihoods and ecosystem services and are considered a major source of fiber and animal nutrients. This work was carried out in Floriano-PI with the objective of evaluating the spatial variability of calcium, aluminum, potential acidity, phosphorus and total organic carbon contents, as well as their correlation with the productivity of a Mombaça grass pasture in a Litholic Dystrophic Neosol. For data analysis, the methods of classical statistics, correlation analysis, geostatistical analysis and data interpolation technique were used. The diagnosis of soil fertility shows phosphorus as the most deficient, followed by calcium. The aluminum values and potential acidity are adequate for the good development of Mombaça grass. The variability of the maps shows the heterogeneity of the distribution and concentration of elements in the soil, which makes it possible to apply fertilizers at different rates for its homogenization. Productivity had a strong relationship with calcium and phosphorus contents. The use of geostatistics can be used to optimize Mombaça grass production areas in Litholic Neosols.